Swedish cities now belong to the most segregated in Europe (Sociologisk Forskning, 2017)
This article presents our research on contemporary urban developments in major Swedish cities. First, we present an analysis of new forms of urban governance in major cities, particularly focusing on inner city developments. Second, we present research on the transformation of housing policies and the so-called Million Program. Third, we highlight new conflicts that have emerged as consequences of these developments, including urban collective action.